2019
DOI: 10.1002/bkcs.11932
|View full text |Cite
|
Sign up to set email alerts
|

The Activation of Glycerol Dehydrogenase from Escherichia coli by ppGpp

Abstract: Glycerol dehydrogenase (GldA) from Escherichia coli is a Zn2+‐containing alcohol dehydrogenase which catalyzes the NAD+‐dependent oxidation of glycerol to dihydroxyacetone. In this study, GldA has been cloned, over‐expressed, and isolated by an affinity and an ion‐exchange chromatography. GldA shows a strong intrinsic fluorescence at 320 nm, when excited at 280 nm. The fluorescence intensity decreases in the presence of NAD+, NADH, and dihydroxyacetone, the substrate and products for GldA, which allows us to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Our structures thus show that Tris was bound at the central cleft, including the active site, where it coordinated with the catalytic Zn 2+ as the substrate of GDH does and that they formed a ternary complex with NAD + . The catalytic Zn 2+ coordination of Tris is consistent with the earlier finding that Tris inhibits GDH by competing with glycerol [13]. In addition, a homooctameric assembly of GDH NAD•Tris was also formed by the crystallographic symmetry operations, and the two protomers of GDH NAD•Tris structure had nearly identical conformations, not only for their overall structures, which had a RMSD of 0.4 Å for 367 C α atoms, but also for the β-hairpin.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…Our structures thus show that Tris was bound at the central cleft, including the active site, where it coordinated with the catalytic Zn 2+ as the substrate of GDH does and that they formed a ternary complex with NAD + . The catalytic Zn 2+ coordination of Tris is consistent with the earlier finding that Tris inhibits GDH by competing with glycerol [13]. In addition, a homooctameric assembly of GDH NAD•Tris was also formed by the crystallographic symmetry operations, and the two protomers of GDH NAD•Tris structure had nearly identical conformations, not only for their overall structures, which had a RMSD of 0.4 Å for 367 C α atoms, but also for the β-hairpin.…”
Section: Resultssupporting
confidence: 85%
“…Nonetheless, in all the ASU molecules of our two structures, there were additional electron densities adjacent to the catalytic Zn 2+ , where water molecules were insufficient to fill. Given the crystallization conditions and references showing that Tris can be located at the active site of GDH [13,16], we fitted Tris to the additional electron density maps observed at the active site. To prove the existence of Tris and optimize its positions for the best fit, we utilized calculation of its omit F o À F c map with simulated annealing that minimizes model bias, occupancy refinement for each Tris and dual conformational fitting when necessary.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ppGpp controls bacterial replication, transcription, and translation 12 . In addition, ppGpp directly regulates many enzymes, such as glycerol dehydrogenase, polyphosphate kinase, lysine decarboxylase, DNA primase, and translation factors 13,14 . It has been reported that the regulation of gene expression by SspA requires a functional relA gene, 2 which is responsible for synthesizing ppGpp from GTP/GDP and ATP 15,16 .…”
Section: Introductionmentioning
confidence: 99%